R-HEALS: Sebuah Model Pemuridan Doctrinal-Experiential bagi Pemuda Indonesia di Taiwan pada Era Pascamodern - Destyanto, Twin Yoshua R.; Kristyanto, Twin Hosea W.; Kadarisman, Terry (Veritas : Jurnal Teologi dan Pelayanan, 2023)
Social interaction is one of the factors that determine a person’s spiritual growth. The social interaction style of today’s youth has been influenced by postmodernism. Postmodernism has changed the way humans socialize to become fluid as a result of the emphasis on relativism. One of the countries affected by postmodernism is Taiwan. This is shown by the development of the cohabitation lifestyle and the legalization of same-sex marriage in Taiwan as part of the relativism and human rights championed in postmodernism. Thus, postmodernism can seep in and threaten the spirituality of Christian students from Indonesia in Taiwan. GBI Taiwan Zhongli responded to this threat by formulating a discipleship model called R-HEALS (Reached, Healed, Equipped, and Heals). This study aims to explore the experience of R-HEALS discipleship participants and its impact on them in facing postmodernism. The method used in this research is a qualitative method with a phenomenological approach. The research data was taken from two students who have followed the R-HEALS discipleship model for at least one year. It was found that the doctrinal-experiential aspect of the R-HEALS discipleship model helps young people resist the current postmodernism, even in a liberal country like Taiwan. It can be concluded that R-HEALS can help the church in contributing to restraining the postmodern lifestyle of young Indonesians studying in Taiwan.